Dynamics of The Tranquil Cosmic Web. Issue Volume 11:Issue S308(2015) (12th October 2016) - Nusser, Adi
Abstract: The phase space distribution of matter out to ∼ 100 Mpc is probed by two types of observational data: galaxy redshift surveys and peculiar motions of galaxies. Important information on the process of structure formation and deviations from standard gravity have been extracted from the accumulating data. The remarkably simple Zel'dovich approximation is the basis for much of our insight into the dynamics of structure formation and the development of data analyses methods. Progress in the methodology and some recent results is reviewed.